Meningkatkan Hasil Belajar Siswa dengan Menggunakan Pendekatan Saintifik pada Mata Pelajaran Matematika di Kelas V SD Negeri 064974 Medan Tembung T.A 2020/2021 - Irmayanita (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2022)
The subjects of this study were fifth grade students of SD Negeri 064974 Medan Tembung T.A 2020/2021 with a total of 30 students consisting of 18 female students and 12 male students. While the object of this research is student learning outcomes in Mathematics subjects, the subject matter of fractional arithmetic operations using a scientific approach. This type of research is Classroom Action Research (CAR) with data collection tools used are tests and observations for teachers and students. This research was conducted through 2 cycles consisting of 4 meetings.The results of the study indicate that using learning with a scientific approach can improve student learning outcomes. Based on the results of the study, it was found that the average score of students at the time of the initial test (pre-test) before being given the action was 54.73 and only 10 students who finished with classical learning completeness were 33.33% and were declared incomplete. In the first cycle the average value increased to 62.73 and 16 students who completed the classical learning completeness level of 53.33%. In the second cycle the average value of the class increased to 76.63 and the students who finished studying were 28 students with a classical learning completeness level of 93.33%. While the attitude assessment (affective) in the first cycle was 2.45 (Enough) but after the improvement in the second cycle it became 3.19 (Very Good). The assessment of skills (psychomotor) in the first cycle was 2.48 (Enough), but after improvements were made in the second cycle it became 3.26 (Very Good). In addition, in the first cycle the teacher's ability to use a scientific approach was quite good (meeting I 2.83 and meeting II 3.00) but there was an increase in cycle II the teacher's ability to be very good (meeting I 3.67 and meeting II 3.83).